Биогеохимические исследования в системе "река Анадырь – Берингово море" в летний период 2013 г.; Океанология; Т. 55, № 5 - Дударев О. В. Олег Викторович; Чаркин А. Н. Александр Николаевич; Пипко И. И. Ирина Ивановна; Пугач С. П. Светлана Петровна; Космач Д. А. Денис Алексеевич; Черных Д. В. Денис Вячеславович; Семилетов И. П. Игорь Петрович; Винников А. В. (2015, 2015)
Заглавие с экрана